2006
DOI: 10.1038/ni1367
|View full text |Cite
|
Sign up to set email alerts
|

Key function for the Ubc13 E2 ubiquitin-conjugating enzyme in immune receptor signaling

Abstract: The Ubc13 E2 ubiquitin-conjugating enzyme is key in the process of 'tagging' target proteins with lysine 63-linked polyubiquitin chains, which are essential for the transmission of immune receptor signals culminating in activation of the transcription factor NF-kappaB. Here we demonstrate that conditional ablation of Ubc13 resulted in defective B cell development and in impaired B cell and macrophage activation. In response to all tested stimuli except tumor necrosis factor, Ubc13-deficient cells showed almost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
281
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 245 publications
(295 citation statements)
references
References 57 publications
10
281
4
Order By: Relevance
“…IkBa degradation in response to LPS is also impaired in macrophages and splenocytes from Ubc13 +/-mice [43]. In contrast, Yamamoto et al revealed that Ubc13-deficient murine embryonic fibroblasts show normal activation of NF-kB in response to IL-1, whereas JNK activation is impaired [44]. Furthermore, TRAF6 poly-ubiquitination and TAK1 activation are normal in Ubc13-deficient cells; however, IKKg poly-ubiquitination upon IL-1 stim- Here IRAK-1 is K63-polyubiquitinated by Pellino, which is itself phosphorylated by IRAK-1.…”
Section: Il-1r and Tlr-4 Signaling To Nf-kbmentioning
confidence: 98%
See 2 more Smart Citations
“…IkBa degradation in response to LPS is also impaired in macrophages and splenocytes from Ubc13 +/-mice [43]. In contrast, Yamamoto et al revealed that Ubc13-deficient murine embryonic fibroblasts show normal activation of NF-kB in response to IL-1, whereas JNK activation is impaired [44]. Furthermore, TRAF6 poly-ubiquitination and TAK1 activation are normal in Ubc13-deficient cells; however, IKKg poly-ubiquitination upon IL-1 stim- Here IRAK-1 is K63-polyubiquitinated by Pellino, which is itself phosphorylated by IRAK-1.…”
Section: Il-1r and Tlr-4 Signaling To Nf-kbmentioning
confidence: 98%
“…65,2008 Review Article 2967 ulation is impaired [44]. As UbcH7 is also known to mediate K63-linked poly-ubiquitination of TRAF6 [45], there might be redundancy for TRAF6 autoubiquitination, but not for IKKg poly-ubiquitination by TRAF6.…”
Section: Il-1r and Tlr-4 Signaling To Nf-kbmentioning
confidence: 99%
See 1 more Smart Citation
“…NEMO also has the potential to bind K63-linked polyubiquitin chains, but the affinity of NEMO for linear polyubiquitin chains seems to be even greater than for K63-linked ubiquitin chains (20,21). It was shown that TAK1 and UBC13 are essential for the responses of macrophages and B cells to TLR and Ag receptor stimulation (22)(23)(24), leading to the activation of Ag-specific immune responses. Nevertheless, mouse embryonic fibroblasts lacking TAB2 showed normal NF-kB activation in response to TNF and IL-1b (24,25).…”
mentioning
confidence: 99%
“…37 In addition, IKKγ has been shown to control the activation of JNK and p38 MAPK by cooperating with Ubc13 E2 ubiqutin-conjugating enzyme. 38 JNK and p38 MAPK are well-known cytokineresponsive MAPKs and are coordinatively activated with NF-κB in response to a wide range of stimuli. Of note, JNK and p38 MAPK are also known to regulate Fra-1, which Chang et al 35 have shown is dysregulated in IKKγ-DN-expressing cells.…”
Section: Discussionmentioning
confidence: 99%